Cross-flow fan on multi-dimensional airflow field of air screen cleaning system for rice grain - Liang, Yaquan; Tang, Zhong; Zhang, Hao; Li, Yaoming; Ding, Zhao; Su, Zhan (International Journal of Agricultural and Biological Engineering, 2022)
With the advancement of agricultural mechanization and the development of combine harvesters, cleaning devices play a very important role in the grain harvesting process. In this study, the DFPF-25 type material floating velocity measuring device was used to measure the suspension velocity of each component of the grain material. Secondly, the DFQX-3 cleaning device was used to conduct the airflow field test, then the fluid simulation of the cleaning shoe was carried out. The results showed that the simulation and experimental results were in a good agreement under the conditions of single fan and double fan. The high-speed flow velocity formed by the double fan system at the tail of the cleaning shoe was 4.76 m/s (simulation) and 4.03 m/s (experiment), which had outstanding cleaning effects on unfilled grains, long stems, and short stems. To sum up, the installation of the cross-flow fan at the rear of the cleaning shoe has a positive effect on the cleaning effect of the combine harvester, and the double-fan cleaning structure composed of the cross-flow fan and the centrifugal fan can significantly improve the cleaning effect.Keywords: double-fan structure, CFD, cross-flow fan, velocity contour, rice grainDOI: 10.25165/j.ijabe.20221504.6949Citation: Liang Y Q, Tang Z, Zhang H, Li Y M, Ding Z, Su Z. Cross flow fan on multi-dimensional airflow field of air screen cleaning system for rice grain. Int J Agric & Biol Eng, 2022; 15(4): 223–235.